First measurement of the ltl dependence of incoherent J/ψ photonuclear production - Acharya, Shreyasi (2024)
The first measurement of the cross section for incoherent photonuclear production of J=ψ vector mesons as a function of the Mandelstam jtj variable is presented. The measurement was carried out with the ALICE detector at midrapidity, jyj < 0.8, using ultraperipheral collisions of Pb nuclei at a center-of-mass energy per nucleon pair of √sNN=5.02  TeV. This rapidity interval corresponds to a Bjorken-x range ð0.3–1.4Þ × 10−3. Cross sections are given in five jtj intervals in the range 0.04 < jtj < 1 GeV2 and compared to the predictions by different models. Models that ignore quantum fluctuations of the gluon density in the colliding hadron predict a jtj dependence of the cross section much steeper than in data. The inclusion of such fluctuations in the same models provides a better description of the data.